Racial disparities in comorbidity and severe maternal morbidity/mortality in the United States: an analysis of temporal trends. (1st November 2017) - Metcalfe, Amy; Wick, James; Ronksley, Paul
Abstract: Introduction: Severe maternal morbidity and mortality have increased in the USA in recent years. This trend has not been consistent across all racial groups. The reasons behind this, and the relation between preexisting conditions, pregnancy‐associated disease and severe maternal morbidity/mortality, have not been fully explored. Material and methods: Annual data on delivery hospitalizations between 1993 and 2012 were obtained from the Nationwide Inpatient Sample (NIS), representing a 20% sample of hospital discharges from across the USA. Chi‐square tests for trend were used to examine temporal patterns in the proportion of pregnancies affected by comorbidities as defined by the Obstetric Comorbidity Score and were stratified by maternal race. Logistic regression was used to determine the impact of temporal increases in comorbidity on severe maternal morbidity/mortality. Results: In 1993, 34.3% of pregnancies had a comorbidity score of ≥1; this significantly increased to 44.1% by 2012 ( p < 0.001). Baseline differences were observed between all races (Whites 33.7%, Blacks 34.5%, Hispanics 28.0%, Asian/Pacific Islanders 28.1%). Although significant increases were observed for all races, the relative rate of change was lowest for Whites (26.1% increase) and highest for Asian/Pacific Islanders (49.1% increase). The odds of severe maternal morbidity/mortality have steadily increased over time; however, adjustment for Obstetric Comorbidity Score significantly attenuates this correlation. Conclusion: The rate of both preexisting comorbidities and pregnancy‐associated disease is increasing in pregnant women in the USA and varies substantially by race. These trends provide valuable insight into the increasing complexity of pregnancy in the USA and explain a proportion of the observed increase in severe maternal morbidity/mortality.